Effectiveness of the Platelet Rich Fibrin with Suture and without Suture on Postoperative Complications Following Removal of Lower Third Molars - Mohammed, Nezar Sheikh Ahmed; Hamaamin, Nzar Abdulqadr (Sulaimani Journal for Pure and Applied Sciences, 2022)
Background: The removal of impacted 3rd molar is a traumatic surgical procedure that may lead to some postoperative sequelae such as pain, swelling, and trismus. The aim of this study was to evaluate the effects of PRF with suture, and without suture, on post-operative complications after removal of 3rd molars. Patients and Materials: This study enrolled 60 patients with partially impacted lower third molars at three centers; Postgraduate Clinic- Department of Oral and maxillofacial Surgery/College of Dentistry/ University of Sulaimani, Private Dental and Maxillofacial Clinic, and Maxillofacial Unit of Kalar General Hospital from November of 2021 till April of 2022. They were randomly allocated into 3 groups of 20 patients each. Group Ӏ was managed by PRF with suture, group ӀӀ was managed by PRF without suture and group ӀII was left without PRF and without suture. Pain, swelling, and maximum interincisal mouth opening were evaluated after the procedure at 1st, 3rd and 7th post-operative days. Results: In terms of pain (p=0.06), trismus (p=0.71), and swelling (p=0.05), there were no statistically significant differences between the study groups and the control group. In contrast to the control group, the values of the three parameters connected to the study groups were lower. In the group of PRF with suture, Visual Analogue Scale (VAS) pain scores on the 3rd and 7th days were significantly (P=0.008 and P=0.038, respectively) less than other groups. Regarding swelling and trismus, there was no significant correlation (P>0.05) between groups. Conclusions: Application of PRF with and without suture had no significant effects on postoperative complications such as pain, swelling, and trismus following removal of partially impacted third molars.
Keywords: Impacted third molar; Postoperative Complications; Platelet rich fibrin; Suture; Prospective study